Antenna Design for Directivity-Enhanced Raman Spectroscopy. (25th March 2012) - Ahmed, Aftab; Pang, Yuanjie; Hajisalem, Ghazal; Gordon, Reuven
Abstract : Antenna performance can be described by two fundamental parameters: directivity and radiation efficiency. Here, we demonstrate nanoantenna designs in terms of improved directivity. Performance of the antennas is demonstrated in Raman scattering experiments. The radiated beam is directed out of the plane by using a ground plane reflector for easy integration with commercial microscopes. Parasitic elements and parabolic and waveguide nanoantennas with a ground plane are explored. The nanoantennas were fabricated by a series of electron beam evaporation steps and focused ion beam milling. As we have shown previously, the circular waveguide nanoantenna boosts the measured Raman signal by 5.5x with respect to a dipole antenna over a ground plane; here, we present the design process that led to the development of that circular waveguide nanoantenna. This work also shows that the parabolic nanoantenna produces a further fourfold improvement in the measured Raman signal with respect to a circular waveguide nanoantenna. The present designs are nearly optimal in the sense that almost all the beam power is coupled into the numerical aperture of the microscope. These designs can find applications in microscopy, spectroscopy, light-emitting devices, photovoltaics, single-photon sources, and sensing.